Evaluación del tiempo termal óptimo en kikuyo (Pennisetum clandestinum) para bovinos pastoreados en la hacienda “Ayahurco”, cantón Mejía - Galarza Tutillo, Cristina Elizabeth (2015)
This research took place at the Pichincha Province, Canton Mejia Hacienda "Ayahurco", in order to make an assessment of the optimal thermal time Kikuyu (Pennisetum clandestinum) for feeding grazed cattle, in order to determine the amount of accumulated temperature in relation to the FDN pasture for regrowth to have consistent quality, cost-benefit determine and assess the body condition of the animals and determining the feasibility of the research for which bromatológicos and laboratory tests were used. In one of the paddocks of Finance proceeded to put 2 thermometers high and low temperatures to 4cm soil, the animals must comply with parameters weighing between 400kg and 500kg, with an output not exceeding 25 liters / day. 10 animals were selected and the framework for identification....